Trends in Road Traffic Deaths in Yazd, Iran, 2004 - 2010 - Mirzaei, Mohsen (Arch Trauma Res, 2016)
BACKGROUND: Road traffic deaths are a considerable public health problem and a major source of lost financial and human resources. Most mortality occurs in low- and middle-income countries. OBJECTIVES: This study aimed to measure road traffic fatality rates and years of lost life, and also to depict a view of trends in road traffic deaths from 2004 to 2010 in Yazd city, a province in central Iran. MATERIALS AND METHODS: This retrospective case study analyzed road traffic deaths that were classified under the V01 - V99 codes of the ICD-10 in Yazd province from March 2004 to March 2010, using data that were collected from the death registration system of the Yazd province health center. Cases were classified according to age, sex, time of year, and residence (urban vs. rural). Years of lost life and road fatality rate per 100,000 people were calculated. Data were analyzed using chi-square test and ANOVA with SPSS 16. RESULTS: During the seven-year period of this study, 3,028 people in Yazd province died due to road traffic accidents (9.1% of total deaths in the province). Most deaths occurred among people aged 20-24 (15%), men (82.7%), and urban residents (82.6%). Total years of lost life (YLL) were 73,875 (60,337 and 13,489 in men and women, respectively). The road traffic fatality rate per 100,000 was 47.6 in 2004 and 37.6 in 2010. In the study period, the rate of traffic fatalities decreased for men (from 77.9 to 68.5) but this is not the case for women (from 14.8 to 19.2). Road traffic deaths peaked every summer. CONCLUSIONS: Despite the overall reduction trend, the road traffic fatality rate in Yazd province is still alarmingly high compared to national and global data. In addition, the female population shows increasing death rates. These findings can serve as a basis for health care professionals and policymakers to conduct preventive measures, especially during summer, and plan specifically for reducing fatalities in the female population.